Kovar Tube as a Potential Catalyst for Conversion of Tar Produced from Biomass Gasification - Aljbour, Salah H.; Kawamoto, Katsuya; Tagawa, Tomohiko; Yamada, Hiroshi (Видавництво Львівської політехніки, 2022)
Попередньо окиснена трубка з ковару використана як каталізатор риформінгу для перетворення нафталену. За умов сухого риформінгу можна досягти конверсії нафталену 24,7%. За додавання до генераторного газу водяної пари в об’ємному співвідношенні 0,06 і 0,11 досягається конверсія нафталену 36,6 і 42,3%, відповідно. Підвищення температури риформінгу до 1173 К збільшує каталітичне видалення нафталену до 91,5%. Величини енергії активації та передекспоненційного множника становлять 136 кДж/моль і 3,07107 см3см-2хв-1, відповідно.

A pre-oxidized Kovar tube was employed as a reforming catalyst for the conversion of naphthalene. Under dry reforming condition, 24.7% naphthalene conversion could be achieved, whereas 36.6 and 42.3 % naphthalene conversion could be achieved when steam was added to the producer gas at the volume ratio of 0.06 and 0.11, respectively. Increasing the reforming temperature to 1173 K enhanced the catalytic removal of naphthalene to 91.5%. The activation energy and frequency factor values were found to be 136 kJ/mol and 3.07107 cm3cm-2min-1, respectively.
Трубка з ковару як потенційний каталізатор для перетворення дьогтю, отриманого в результаті газифікації біомаси
Keywords: трубка з ковару; дьоготь; нафтален; каталізатор; газифікація; Kovar tube; tar; naphthalene; catalyst; gasification